(untitled) (Revista de Biología Marina y Oceanografía, 2021)
The objectives of this research were to estimate the abundance of the main groups of planktonic mollusks (meroplanktonic larvae, holoplanktonic gastropods and cephalopod paralarvae), and relate these groups to the physical-chemical water properties along a longitudinal gradient between Caldera, on the coast of mainland Chile, and the Easter Island ecoregion (Rapa Nui Island and Salas y Gómez Island), in the Southeast Pacific Ocean. Plankton samples were collected over the course of the CIMAR 21-Islas Cruise, from October to November 2015, at 33 oceanographic stations via vertical hauls of a WP2 net (180-µm mesh size) from a maximum depth of 300 m to the sea surface. Mollusks were sorted, counted and initially assigned to Class rank, later being identified to lower taxonomic ranks. Planktonic mollusks were obtained at all stations, and were composed of 92.7% of Gastropoda and 7.3% of Bivalvia. The total abundance of mollusks varied between 55 and 4,922 individuals 100 m-3.Euthecosomate gastropods exhibited the highest occurrence within the oceanic area. Meanwhile, no paralarvae were captured. Differences in the composition of planktonic mollusks between the continental and oceanic zones were evident. Bivalve larvae increased their abundance in warmer, salty and vertically mixed waters. These results are the first record of meroplanktonic mollusks in waters near the Chilean oceanic islands, and suggest that planktonic mollusks display spatial variation at the scale of the South Pacific Basin, which could be related to the hydrographic conditions and the water column structure.